Tantangan Yang Dihadapi Oleh Organ Pemerintah Daerah Dalam Menjalankan Kedudukan Dan Kewenangannya Di Era Desentralisasi - Asri Agustiwi; Aprillia Nur Hidayah Kusuma (Universitas Sunan Drajat Lamongan, Indonesia, 2026)
The implementation of regional governance in Indonesia after the reformation, particularly after the implementation of the decentralization system, has granted broader authority to regional governments in managing government affairs. This study aims to explain the position and authority of each regional government organ, namely the regional head, the Regional People's Representative Council (DPRD), and regional apparatus, in the implementation of regional governance in the era of decentralization. This research uses a normative approach by examining related legislation, such as Law No. 23 of 2014 on Regional Government. This study aims to analyze and identify the challenges faced by local government bodies in carrying out governance in the era of decentralization. The results indicate that the regional head plays the role of executive leader responsible for implementing government policies, the Regional People's Representative Council (DPRD) carries out legislative, budgetary, and supervisory functions, while the regional apparatus functions as technical implementers. However, a number of challenges such as lack of coordination between organs, limited resources, and potential conflicts of interest are becoming a problem.